2015
DOI: 10.18203/2320-6012.ijrms20151153
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of hyperbaric bupivacaine versus hyperbaric bupivacaine and fentanyl (12.5 mcg) in subarachnoid anesthesia for lower abdominal and lower extremity surgeries

Abstract: INTRODUCTIONSpinal anesthesia is a safe, convenient and economical form of regional anesthesia technique. It results in sympathetic blockade, sensory analgesia, and motor blockade depending on the dose, concentration or volume of local anesthetic agent administered.1 Bupivacaine is the most common local anesthetic agent used. The desired effect is to block the transmission of nerve signals to and from the affected area. Spinal anesthesia has many advantages over general anesthesia which makes it the anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It has been shown that the addition of 25 μg of fentanyl to 10 mg of 0.5% HB significantly prolonged the duration of complete analgesia, as well as effective analgesia, thus reducing the need for an early use of postoperative analgesics without an increase in adverse effects due to administration of fentanyl in spinal anesthesia during these type of surgeries. [ 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the addition of 25 μg of fentanyl to 10 mg of 0.5% HB significantly prolonged the duration of complete analgesia, as well as effective analgesia, thus reducing the need for an early use of postoperative analgesics without an increase in adverse effects due to administration of fentanyl in spinal anesthesia during these type of surgeries. [ 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the synergism and efficacy of opioid and local anesthetics when used in combination, for the control of PONV. Although in some cases, medication alone appears to be similar in efficacy when used as individual agents; [ 23 26 27 ]the addition of opioids such as fentanyl to HB in spinal anesthesia reduces latency, significantly prolongs duration and improves the efficacy of analgesia, when compared to bupivacaine alone. [ 28 ] Being an opioid, Fentanyl exerts its effects when combined with opioid receptors in the dorsal horn of the spinal cord and may have supraspinal action and propagation.…”
Section: Discussionmentioning
confidence: 99%
“…The desired effect is to block the transmission of nerve signals to and from the affected area. 1 The increasing acceptance of subarachnoid block can be attributed to the simplicity of the technique and equipment, economy, maintenance of consciousness and spontaneous respiration, muscle relaxation, minimal disturbances of body chemistry, less intra operative bleeding, decreased incidence of post-operative nausea, vomiting and aspiration, prolonged post-operative analgesia and a pleasant recovery from anaesthesia. 2 However, these advantages are oppressed by limited duration of action of subarachnoid block and by uncomfortable postoperative period when its action wears off.…”
Section: Introductionmentioning
confidence: 99%